RANCANG BANGUN DIGESTER SEMI KONTINYU PADA PRODUKSI BIOGAS DAN PUPUK ORGANIK DARI SAMPAH ORGANIK - Ikhsan, Diyono; Handayani, Dwi; Murni, Murni (METANA, 2013)
Abstract Production of biogas and organic fertilizer from organic waste is done by creating a semi-continuous digester design is a flat pipe and operate continuously or bait can be inserted periodically every day, and its products can be taken periodically at any time. At the optimum residence time can be designed digester volume corresponding to a certain capacity, the variation ratio of the length and diameter of the pipe, whichever is best for optimum biogas production. Outcomes of the research is a prototype digester flat pipes that can operate semi-continuous along with its performance test. Design semi-continuous digester using pralon pipe diameter of 6 in, with the length of each digester m A = 2, B = 4 m, and C = 6 m, equipped hopper for feeding suspension, bulkhead divider so that biogas does not leak, and the stirrer tank float models. The results showed that the biogas production on day 7 to day 30, there was an increase biogas production sharply, after it approaching constant and up to 60 days tended to decline. In the longer digester (B and C) there are fluctuations in the production of biogas. From the graph the relationship between the capacity of the biogas production time from day 1 to day 60 following polynomial equation with a similar pattern, for the digester with the equation y = A + 2,287x -0,026x2 - 8.577 (RÂ¬2 = 0.966); digester B with the equation y = -0,026x2 2,297x + - 8.683 (R 2 = 0.963); and digester C with equation y = -0,025x2 2,232x + - 8.886 (R 2 = 0.962). Mud coming out at the end of the digester after 30 days was collected and dried as organic fertilizer. Results of laboratory analysis, showed the water content 10.72%, 44.05% organic C content, C / N Ratio 25.70, total P2O5 content of 0.67% and 7.71% N levels. This suggests that these parameters meet the quality standards of organic fertilizers except C / N Ratio greater. But this is not a problem because the levels of organic C and N levels separately meet quality standards. Keywords: digester, biogas, organic fertilizer